Recommended Place Naming Methods for the Democracy Initiative and UVA Equity Center - Milone, William; Rothfleisch, Jessica; Mortimer, Emily (University of Virginia, 2021)
This report describes research conducted in partnership with student consultants Will Milone, Emily Mortimer, and Jessie Rothfleisch and the University of Virginia Equity Center’s Democratization of Data initiative as part of the students’ final project for the UVA course, PLAN 3813/6813: Community Engaged Methods: Tools for Equitable Research & Practice. The purpose of this research was to evaluate existing methods of participatory place naming practices and provide a set of recommendations for executing participatory place naming of census tract areas in the counties surrounding the city of Charlottesville. The UVA Equity Center created a digital Equity Atlas which provided demographic data for census tracts in the Charlottesville and Albemarle areas. In visualizations of this data, census tracts were given names without input from residents. In most visualizations of neighborhood data, census tracts are used as a proxy for the neighborhood. However, “residents and local organization[s’]... neighborhood perceptions, activities and networks do not necessarily comport with census boundaries” (Coulton et al 2004). Therefore, using participatory place naming to create labels for census tracts in data visualizations will allow maps to be more meaningful to residents and the general public. As student partners, we researched topics adjacent to participatory place naming such as defining neighborhood boundaries, critical and urban toponymy, and participatory mapping in order to identify case studies of similar projects to inform our final recommendations for a place naming strategy. This report will discuss three case studies, evaluating the methods they employed and highlighting the strengths and weaknesses of those methods. Our criteria for evaluating methods will consider ideas such as power sharing, equity, and level of participatory engagement. Finally, we will discuss how the methods and analysis used in these case studies can be applied to the Equity Center’s Place Naming project, in order to suggest a “documented, valid, and reproducible method for community identification of markers and alternative unit names, particularly those that are meaningful to minoritized populations” (UVA Equity Center 2021).
Original submission date: 2021-12-11T03:14:03Z
Keywords: Participatory Mapping; Critical Toponymy; Place Naming; Census Tract